2008
DOI: 10.1007/s00264-008-0696-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of hook plate versus tension band wire in the treatment of unstable fractures of the distal clavicle

Abstract: Fifty-two patients with unstable fractures of distal clavicle treated by open reduction and internal fixation with hook plates or tension band wires were retrospectively reviewed. The 52 patients were divided into two groups based on the method of treatment. The hook plate (HP) group included 32 patients and the tension band wire (TBW) group included 20 patients. Both groups were similar in respect to injury mechanisms, compounding medical conditions, and shoulder score (p>0.1). However, hook plating had a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 16 publications
2
57
0
2
Order By: Relevance
“…Complications reported with this design have also been relatively frequent, including implant failure and metaphyseal fracture, impingement, rotator cuff tears or even hook migration and acromial fracture as the implant penetrates the subacromial space and require plate removal. It is therefore important to exercise caution when using hook plate [6][7][8][9][10][11][12][13]. In a recent study, Tan et al [26] reported 74 % of patients in the hook plate group had mild to severe shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complications reported with this design have also been relatively frequent, including implant failure and metaphyseal fracture, impingement, rotator cuff tears or even hook migration and acromial fracture as the implant penetrates the subacromial space and require plate removal. It is therefore important to exercise caution when using hook plate [6][7][8][9][10][11][12][13]. In a recent study, Tan et al [26] reported 74 % of patients in the hook plate group had mild to severe shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…Since not all studies reported the functional outcome scores of the distal clavicle fractures and they used different functional evaluation instruments, it was difficult to analyse and compare the function between the different treatment modalities. Consequently, we reviewed and compared the functional outcome scores evaluated by Constant score between the hook plate group (nine studies) [6,7,[9][10][11][12][13]31, present study] and the locking plate group (eight studies) [14][15][16][17][18][19][20]30, present study] in distal clavicle fractures. The mean Constant scores were 91.9 and 93.6 in the hook plate and locking plate groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Lee at al. [26] described the advantageous role of hook plate fixation in their comparative study between hook plate and tension band. Andersen et al [27] reported 94% union rate with precountered superior locking plate fixation for displaced distal clavicle fractures.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have reported that mid-shaft fractures have a higher incidence of symptomatic non-union than previously thought [12][13][14][15]. Some authors now recommend acute fixation of displaced mid-shaft fractures [12,13], and some recommend acute fixation of some lateral third fractures [16,17]. Most clavicle fractures are treated 'conservatively' in our institution, and we wanted to review this policy.…”
Section: Introductionmentioning
confidence: 99%